Economically Important Macrophytes of Chilika Lagoon, Odisha, India - Hemant Kumar Patra, Kalpita Bhatta (International Journal of Advanced Science and Technology, 2020)
Macrophytes have efficacy to be used as food, fodder, medicine and other miscellaneous uses. They are important bio-resources for direct economic use and also play an important role in the lake ecosystem.  Macrophytes act as producer, habitat for migratory bird and carbon sequestration. In the present investigation a check list of economically important macrophytes of Chilika lagoon was prepared and their categorization in various aspects was documented.  Data were collected with the help of standardized questionnaire. Interviews were made with local healers, traditional practioners and fisher folk. A total of 25 plants were reported which includes dicotyledons, monocotyledons and pteridophytes. Mostly leaves and shoots were found to be used by the local inhabitants for various purposes like vegetables as well as medicines. The collected specimens were identified and deposited in the Herbarium of the Botany Department, Centurion University of Technology and Management. Some important plants are Eichhornia crassipes, Ceratophyllumdemersum, Ipomoea aquatica, Aponogetonatans , Alternanthera sessilis  and Nymphoides indica . The data obtained in the present work will be useful in documenting the economical important plant species of Chilika lagoon for further study and for ensuring sustainable livelihood of the local people. The indigenous knowledge gained will be helpful in conserving the native threatened wetland species.